1994
DOI: 10.1111/j.1151-2916.1994.tb07094.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxygen in Microstructure Development at Solid‐State Diffusion‐Bonded Cu/α‐Al2O3 Interfaces

Abstract: Role of Oxygen in Microstructure Development atSo I id -S t a t e D iff u s i o n -Bonded C u/a -A I 0 I n t e r f aces Microstructure development at solid-state diffusion-bonded Cda-Al,O, interfaces has been studied using optical and electron microscopy. High-purity Cu foil was bonded between basal-oriented a-Al,O, single-crystal plates at 1040°C for 24 h in a vacuum of -1.3 X Pa (1 X lo-' torr). Optical microscopy of as-bonded specimens revealed a large Cu grain size, fine pores, and long needles of Cu,O at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In the work of Rogers et al [71], cuprous oxide needles were present at the interface between 99.95% pure copper and sapphire after 24 h hv diffusion bonding at 1040°C even though the ambient p O 2 during diffusion bonding (≈3 × 10 -10 atm) was well below the copper-cuprous oxide equilibrium p O 2 (≈1.6 × 10 -6 atm). s The copper foil was found to contain ≈1200 atomic ppm (ppma) oxygen.…”
Section: Role Of Impurities and Interphasesmentioning
confidence: 95%
See 2 more Smart Citations
“…In the work of Rogers et al [71], cuprous oxide needles were present at the interface between 99.95% pure copper and sapphire after 24 h hv diffusion bonding at 1040°C even though the ambient p O 2 during diffusion bonding (≈3 × 10 -10 atm) was well below the copper-cuprous oxide equilibrium p O 2 (≈1.6 × 10 -6 atm). s The copper foil was found to contain ≈1200 atomic ppm (ppma) oxygen.…”
Section: Role Of Impurities and Interphasesmentioning
confidence: 95%
“…Studies by Rogers et al [71] and Rühle et al [57] have shown that the levels of dissolved oxygen in even high-purity copper foils are sufficient to induce formation of interphases that impact the mechanical properties of copper/sapphire assemblies. In the work of Rogers et al [71], cuprous oxide needles were present at the interface between 99.95% pure copper and sapphire after 24 h hv diffusion bonding at 1040°C even though the ambient p O 2 during diffusion bonding (≈3 × 10 -10 atm) was well below the copper-cuprous oxide equilibrium p O 2 (≈1.6 × 10 -6 atm).…”
Section: Role Of Impurities and Interphasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition can be determined from the intensity of the ionization edges which are element specific. Furthermore, the energy-loss near-edge structure (ELNES) in the region from the onset of the edge to approximately [20][21][22][23][24][25][26][27][28][29][30] eV above the edge contains information about the bonding and the electronic structure [1]. Different oxidation states of metals can be distinguished either by chemical shifts or by changes in the shape of the absorption edge.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the processing conditions, either an atomically abrupt interface or reaction layers are formed. Possible phases in the Cu-Al-0 system are the two aluminates CuA102 and CuA1204 [22]. Formation of these compounds at the interface is only expected for bicrystals prepared in a non reducing atmosphere [23].…”
Section: Introductionmentioning
confidence: 99%